Reproducibility study of four‐dimensional flow MRI of arterial and portal venous liver hemodynamics: Influence of spatio‐temporal resolution. Issue 2 (9th September 2013) - Stankovic, Zoran; Jung, Bernd; Collins, Jeremy; Russe, Maximilian F.; Carr, James; Euringer, Wulf; Stehlin, Lena; Csatari, Zoltan; Strohm, Peter C.; Langer, Mathias; Markl, Michael
<x xml:space="preserve">Abstract</x> Purpose To evaluate influence of variation in spatio‐temporal resolution and scan‐rescan reproducibility on three‐dimensional (3D) visualization and quantification of arterial and portal venous (PV) liver hemodynamics at four‐dimensional (4D) flow MRI. Methods Scan‐rescan reproducibility of 3D hemodynamic analysis of the liver was evaluated in 10 healthy volunteers using 4D flow MRI at 3T with three different spatio‐temporal resolutions (2.4 × 2.0 × 2.4 mm3, 61.2 ms; 2.5 × 2.0 × 2.4 mm3, 81.6 ms; 2.6 × 2.5 × 2.6 mm3, 80 ms) and thus different total scan times. Qualitative flow analysis used 3D streamlines and time‐resolved particle traces. Quantitative evaluation was based on maximum and mean velocities, flow volume, and vessel lumen area in the hepatic arterial and PV systems. Results 4D flow MRI showed good interobserver variability for assessment of arterial and PV liver hemodynamics. 3D flow visualization revealed limitations for the left intrahepatic PV branch. Lower spatio‐temporal resolution resulted in underestimation of arterial velocities (mean 15%, P < 0.05). For the PV system, hemodynamic analyses showed significant differences in the velocities for intrahepatic portal vein vessels (P < 0.05). Scan‐rescan reproducibility was good except for flow volumes in the arterial system. Conclusion 4D flow MRI for assessment of liver hemodynamics can be performed with low interobserver variability and good reproducibility. Higher spatio‐temporal resolution is necessary for complete assessment of the hepatic blood flow required for clinical applications. Magn Reson Med 72:477–484, 2014. © 2013 Wiley Periodicals, Inc.